Antibody response to phenolic glycolipid I in inbred mice immunized with Mycobacterium leprae. - Teuscher, C (1985)
The level of circulating antibody to phenolic glycolipid I of Mycobacterium leprae was determined in 18 inbred strains of mice after immunization with M. leprae organisms. By using a solid-phase radioimmunoassay with phenolic glycolipid I as test antigen, a continuous distribution of antibody levels ranging from high to low was observed. The level was found to be controlled by multiple genes, including both H-2 complex- and Igh allotype complex-linked genes. Low antibody response to phenolic glycolipid I was shown to be inherited as a dominant trait in three combinations of high X low responder F1 progeny.